Combined method of colon microbiota correction after colon x-ray in children with chronic colostasis (Bangladesh Journal of Medical Science, 2023)
Objective: The problem of chronic colostasis is especially relevant in children. Numerous research studies have been devoted to this type of pathology, but until now, no final solution has been proposed both in traditional therapy and surgical treatment. The research aimed to study the state of intestinal microbiota in children with chronic colostasis in preparation for irrigation and to evaluate the combined method of its correction by oral and rectal probiotic administration.Materials and methods: The study enrolled 100 patients of both genders aged 5-15 years with the diagnosis of chronic colostasis. All patients were divided into main and control groups consisting of 50 people in each one. For the correction of intestine microbiota, the probiotics in the main group were administered orally and using enema with direct irrigation of the large intestine cavity after preparation for X-ray analysis, while patients of the control group received probiotics only orally.Results and Discussion:In the main group, the concentration of all types of useful microorganisms in the intestine increased to normal values after the correction, the number of useful microorganisms is statistically significantly higher, and the number of opportunistic enterobacteria is less in comparison with the those in the control group (p